Prevalence of serum antibodies to bovine herpesvirus-1 in cattle in Galicia (NW Spain) - Eiras, C.; Diéguez, F.J.; Sanjuan, M.L.; Yus, E.; Arnaiz, I. (Spanish Journal of Agricultural Research, 2009)
Infectious bovine rhinotracheitis (IBR) is a highly infectious disease of cattle caused by bovine herpesvirus 1 (BHV-1) that causes considerable economic losses to the dairy and beef industry. This report describes the results of two surveys in which prevalence of serum antibodies against BHV-1 in Galicia (NW Spain) was determined. The first was performed on the entire cattle population of the region (year 2000) and the second on the herds included in a voluntary livestock health programme, which comprises IBR, conducted by a group of farms designated ADSG (Health Defence Groups) in this same region (year 2004). Anti-BHV-1 antibodies were determined by anti-gB ELISA in serum samples from all animals aged over one year in the arearsquo;s dairy and beef herds. Mean individual animal and herd prevalence recorded in 2000 were 38.4% (ranging 37.3%-39.5%; 43.2% dairy, 26.8% beef) and 50.4% (ranging 46.4%- 54.4%; 58.3% dairy, 48.1% beef), respectively. Mean true prevalence by herd and animal for the ADSG farms were 47.2% (44.9%-49.5%; 51.5% dairy, 45.2% beef, 42.3% mixed) and 35.7% (35.3%-36.1%; 37.8% dairy, 33.1% beef, 25.5% mixed), respectively. However, the use of non-maker vaccines make difficult to develop a control and eradication program based on serological analysis.